Boundaries Crossed, at the Interfaces of Morphosyntax, Phonology, Pragmatics and Semantics (Studies in Natural Language and Linguistic Theory,, 2018)
This volume offers a selection of interface studies in generative linguistics, a valuable "one-stop shopping" opportunity for readers interested in the ways in which the various modules of linguistic analysis intersect and interact. The boundaries between the lexicon and morphophonology, between morphology and syntax, between morphosyntax and meaning, and between morphosyntax and phonology are all being crossed in this volume. Though its focus is on theoretical approaches, experimental studies are also included. The empirical focus of many of the contributions is on Hungarian, and several chapters respond to work published by István Kenesei, to whom the volume is dedicated.